Attitudes of Turkish and Moroccan Belgians toward Redistribution and Government Responsibility: The Role of Perceived Discrimination, Generation, and Religious Involvement. Issue 2 (June 2020) - Galle, Jolien; Abts, Koen; Swyngedouw, Marc; Meuleman, Bart
This article contributes to the debate about migration's impact on welfare state support by investigating the welfare opinions of migrants and their descendants. It examines whether experiences of group and individual discrimination explain the welfare attitudes of this group over and beyond classical predictors of self-interest and political ideology. Using survey data from Belgian citizens of Turkish and Moroccan descent, we show that stronger support for redistribution is associated with higher levels of perceived group discrimination, religious involvement, and belonging to the second generation. Preferences of government responsibility, however, are strongly determined by labor market position and left-right ideology.